SOSIALISASI CERDAS BERSOSIAL MEDIA : PROGRAM PENGABDIAN MASYRAKAT DI DESA GOLO KANTAR KECEMATAN BORONG KABUPATEN MANGGARAI TIMUR - Enjel, Anjelina Rero; Obe, Imelda Yonalia; Pena, Veronika Ruba (Merwinspy Publisher, 2025)
The use of social media has become an inseparable part of modern society, including in rural areas such as Golo Kantar Village. However, there are still significant obstacles in the form of a lack of public understanding regarding the ethics of use, personal data security, and the positive and productive use of social media. This condition has the potential to cause various problems such as the spread of inaccurate information, privacy violations, and negative impacts on social relations in the community. To overcome this, this community service program was designed with the aim of increasing the digital literacy of the Golo Kantar Village community through smart social media socialization. The method of implementing this program includes several stages, namely a needs survey aimed at identifying the level of understanding and obstacles of the community regarding social media, compiling and planning socialization materials that are adjusted to local conditions and needs, and preparing supporting logistics so that activities can run effectively. The core activity in the form of interactive socialization is carried out with a participatory approach, inviting the community to discuss and share experiences in using social media wisely. Furthermore, an evaluation of the impact of the program is carried out to measure changes in the level of digital literacy, awareness of digital ethics, and the community's ability to manage personal data security and use social media productively. The expected results of the implementation of this program are increasing awareness and ability of the Golo Kantar Village community in using social media in a responsible, safe way, and supporting self-development and community. Thus, this program not only contributes to reducing the negative risks of using social media, but also supports improving the quality of life and sustainable village development through the use of appropriate and beneficial information technology.